Asymptotic behavior of the logarithmic derivative for entire functions of order zero - Zabolotskyj, M.V.; Mostova, M.R. (Carpathian Mathematical Publications, 2014)
We get an approximation theorem for the logarithmic derivative $F$ of entire functions of order zero and, with it's help, establish the asymptotic of $ F $ outside the exceptional set.